EFFECT OF SOLID LIPID NANOPARTICLE (SLN) AND NANO STRUCTURE LIPID CARRIER (NLC) SYSTEM ON ANTIOXIDANT STABILITY OF TOMATO EXTRACT (LIPID: CETYL ALCOHOL AND ISOPROPYL MYRISTATE) - Sayyidati Aqilah; Esti Hendradi; Noorma Rosita (UPT Penerbitan Universitas Jember)
Tomato extract was known contains manyantioxidants (Chauhan et al., 2010), such aslycopene, that are easily degraded by UV-B rays. Themechanism lycopene as an antiaging is to reduceskin regeneration and increase the thickness of theepidermis (Sahasrabuddhe, 2011). As anantioxidant, lycopene easily degraded when exposedto light, heat, and oxygen (Chauhan et al., 2011).Drug delivery system based on nanolipid carriersystem, such as: Solid Lipid Nanoparticles (SLN) wasappropriate to stabilize lycopene, as lipophilicsubstance (Wissing and Muller, 2003; Helgason etal., 2009; and Okonogi dan Riangjanapatee, 2014).One of the limitations of SLN is the drug moleculethat has been trapped expulsed easily duringstorage. It is caused of the orderdness of lattice lipidcrystal. Replacement part of solid lipid using liquidlipid (called as nanostructure lipid carriers or NLC)can reduce the orderdness of lattice lipid crystall andit will repaired it (Kaur et al, 2015).In this research have been tried to be compared theability of SLN and NLC to improve the stability ofantioxidant tomato extract. Using 20% total amountof lipid, extract tomato-SLN made from cetyl alcoholas solid lipid and extract tomato-NLC made fromdifference ratio between cetyl alcohol and isopropylmyristate (IPM) such as: 9:1 and 7:3. Tween 80 andKollipor were used as surfactant and co-surfactant.IPM was choose because of its enhancer andemollient effect so easily to apply to the skin(Vadgama et al, 2015).